Social networking with IFTTT services - Yong, Lee Sun. (2012)
The purpose of this report is to describe and review the development of if-this-then-that (ifttt) customized website which is going to be used by Nanyang Technological University (NTU) students. The programs which are used in developing this website are Netbeans 7.1, HTTrack and MySQL.